PENGEMBANGAN PERANGKAT PERKULIAHAN IPA 2 DENGAN PENDEKATAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN HIGHER ORDER THINKING MAHASISWA PROGRAM STUDI PENDIDIKAN GURU SEKOLAH DASAR - Wahyu Kurniawati (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2014)
The purpose of this activity is to get the science learning valid and effective in its implementation . The focus of these activities are: developing the materials science learning style with pen Â¬ problem based learning approach to improve higher order thinking skills and test the effectiveness of student learning devices produced in the class . Tests performed on UPY PGSD student class of 2011 . Stages of software development by arranging lectures dimualai Syllabus , Course Implementation Plan , Student Worksheet , Teaching Material and Evaluation Problem . Based on the results of the validation is known that the validity of the lecture ( Va ) is 4.13 are valid criteria . The results of the study Implemantasi known that more than 90 % of students still think the low levels of C1 , C3 C2dan , whereas for C4 to C6 cognitive less than 50 % of students were able to master it on the first meeting . At the second meeting in which the changes occur 76.47 % of the students have been able to think at the level of C3 , C4 at the level of 23.52 % , 20.58 % and 12.76 % levels C5 C6 level at the first meeting where less than 12 % of students who able to think at the level of C4 - C6 . Average percentage of student activities at the Meeting 1 Meeting at 71.12 % and 72.94 % 2 of which included the high category . The device lectures IPA Problem Based Learning Model appropriate if applied in class because > 80 % of students gave positive responses to the lecture model of Problem Based Learning IPA